Psychometric properties of the persian version of the multiple sclerosis work difficulties questionnaire (MSWDQ) questionnaire - Omid Mirmosayyeb; Vahid Shaygannejad; Soroush Najdaghi; Mahsa Ghajarzadeh (International Journal of Preventive Medicine, 2022)
Background: Patients with multiple sclerosis (MS) suffer from a wide range of psychological and physical problems. Employment status is a crucial issue for patients with MS as unemployment while it is not completely evaluated in patients with MS. Objectives: To assess psychometrical properties of the Persian version of the Multiple Sclerosis Work Difficulties Questionnaire (MSWDQ). Methods: One hundred and sixty patients were enrolled. They were asked to fill valid and reliable Persian version of the Fatigue Severity Scale (FSS), social support scale, and Short Form Health Survey (SF-36) and translated version of the MSWDQ questionnaire. Twenty cases filed the questionnaire two weeks later to assess reliability. The intra-class correlation coefficient (ICC), Cronbach's alpha, correlation coefficients were used. Results: Mean age and mean duration of the disease were 36.8 ± 9.1, and 7.5 ± 5.1, respectively. The Cronbach alpha for psychological/cognitive barriers subscale was 0.87, for Physical barriers was 0.83 and for external barriers was 0.86. The Cronbach α for the whole questionnaire was 0.89. There was a significant positive correlation between FSS and MSWDQ score, and a significant correlation with SF-36 and social support. The ICCs of all questions were acceptable. Conclusions: Persian version of MSWDQ questionnaire is a valid and reliable instrument for evaluating work-related problems in patients with MS.